2001
DOI: 10.1046/j.1440-1746.2001.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide, a KATPopener, accelerates restitution of ethanol or indomethacin‐induced gastric ulceration in rats independent of polyamines

Abstract: The K(ATP) channels may play an important role in the gastric mucosal restitution independent of polyamines. Acid inhibition cannot reverse EAGU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
(38 reference statements)
0
27
0
1
Order By: Relevance
“…It has also been shown that NSAIDs contribute to ulcer formation and delay ulcer healing by inhibiting intestinal epithelial cell migration and mucosal restitution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that NSAIDs contribute to ulcer formation and delay ulcer healing by inhibiting intestinal epithelial cell migration and mucosal restitution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Restitution occurs within minutes to hours following injury in vivo or in vitro, because this process requires cell migration but not cell proliferation or differentiation [17][18][19][20]. While it is established that NSAIDs promote ulceration by interfering with restitution [14][15][16], the signaling pathways mediating this effect have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Contact of gastric mucosal epithelium with ethanol results in the release of endothelins, decrease of nitric oxide synthase, and attenuation of nitric oxide synthesis that will lead to reduced blood supply to the gastric mucosal cells. [2,3] Restriction of the microvascular circulation of the gastric epithelium ensures nutrient and oxygen deprivation to the affected mucosae, accumulation of arachidonic metabolites, generation of reactive oxygen species, polymorphonuclear (PMN) infiltration and adhesions, depletion of gastric mucus, plasma leakages of sodium and potassium ions, and edema. [4][5][6] These unfavorable gastric activities may overwhelm the antioxidant capacity of the system, which lead to oxidative stress that could result in gastric cell membrane damage, apoptosis, exfoliation, epithelial erosion, and formation of gastric ulcer.…”
mentioning
confidence: 99%
“…[5] Tissue necrosis factor-α (TNF-α) along with adenosine, histamine, and leukotrienes are considered as the mediators of early vascular injury in ethanol-induced gastric damage. [2,3,7] TNF-α causes polymorphonuclear (PMN) migration through upregulation of the expression of adhesion molecules in neutrophils and endothelial cells. The migration of PMN is an essential ingredient in the several pathways leading to gastric mucosal disruption.…”
mentioning
confidence: 99%
“…In fact, K ATP channel function has been quite extensively studied in several gastrointestinal models. The K ATP channel opener diazoxide has been shown to attenuate the damage and/or accelerate the restitution of indomethacin-and ethanol-induced intestinal and gastric injury in rats and mice (2,87,98,113,114,122,142), whereas K ATP channel inhibition worsened damage parameters. Moreover, the gastroprotective effect of different compounds, such as the steroid saponin hecogenin (122), the antidepressant drug citalopram (124), or prostaglandins (108), seems dependent on K ATP channel function.…”
Section: Mechanisms Responsible For Control Of Cell Migration/prolifementioning
confidence: 99%